Adsorption characteristics of modified sand for the removal of hexavalent chromium ions from aqueous solutions: Kinetic, thermodynamic and equilibrium studies - Yadav S.; Srivastava V.; Banerjee S.; Weng C.-H.; Sharma Y.C. (My University, 2025)
The objective of this study is to investigate the removal of Cr(VI) from aqueous solutions by using modified sand as adsorbent. The modified sand was characterized by Scanning Electron Microscopy (SEM), Energy Dispersive X-ray Analysis (EDX) and FTIR. pH zpc of the raw and modified sands was found to be 6.98 and 6.66, respectively. Removal efficiency of the modified sand was investigated by using batch adsorption experiments. The effect of important parameters such as initial concentration, contact time, adsorbent dosage, pH and temperature on removal of Cr(VI) was investigated. It was demonstrated that the removal efficiency increased from 67.24% to 80.40% by the decreasing initial metal concentration from 15 to 5mgL -1. Effect of pH was investigated by varying the solution pH from 2.0 to 8.0. The optimum pH for adsorption of Cr(VI) on modified sand was found to be 2.5 with a maximum removal of ~80.40%. Extent of removal decreases by increasing the temperature from 25°C to 35°C confirming exothermic nature. Kinetics of removal process was studied by applying pseudo-first order and pseudo-second order models. Pseudo-first order rate constant was found to be 0.037min -1 while the rate constant for pseudo-second order reaction was found to be 0.0236gmg -1min -1 at 25°C. Values of thermodynamic parameters viz. {increment}G°, {increment}H° and {increment}S° were calculated and found to be -3.67kJmol -1, -68.74kJmol -1and -0.243kJmol -1K -1, respectively at 25°C. The values of δG° were found to be negative at all temperatures indicating the spontaneity of the removal process. A negative value of {increment}H° further confirms the exothermic nature of removal process. The experimental data were fitted to Langmuir as well as Freundlich adsorption isotherm equations. The results obtained in the present study show the modified sand to be a better adsorbent for removal of Cr(VI). © 2012 Elsevier B.V.